The ocean we so love - Ho, Yi Dan (Nanyang Technological University, 2022)
The Ocean We So Love is a figurative expression that highlights the challenges our ocean faces. Through acknowledging the charms of the material world- its ephemerality and expendability, this multimedia interactive installation wants to reveal the fraught intersection between man and our ocean bodies. Rocking the structure while discovering waste for waste itself, participants are brought through an experience to understand that marine debris goes nowhere and often ends up as unusable waste. Change in consumption and systemic change needs to happen for the love of our oceans.